(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Questions: What is the modern state of the newly revealed populations of Spinulum annotinum in the Left-Bank Middle-Dnieper? Location: the left bank of the Dnipro River within the Kyiv and Cherkasy Regions (Oblasts), Biloozerskyi National Nature Park. Methods: field surveys, geobotanical methods. Nomenclature: Plants of the World (POWO 2023). Results: Five populations of the protected species Spinulum annotinum (= Lycopodium annotinum) were revealed on the sand terrace of the Dnipro River within the Kyiv and Cherkasy Regions. Populations were from 30 m2 to 200 m2. The populations of S. annotium prefer to grow in such vegetation classes as Alnetea glutinosae. All of them were in the wet habitats, near the forest bogs, swamps or in the moisture depressions of the relief. Ecological conditions, where populations were found, correspond to the ecological regime in other parts of the species’ range: faintly acid and constantly wet soils. Most plants were in the vegetative phenophase, but the plants with sporangia were found in each population too. Conclusions. All the revealed populations of Spinulum annotinum are associated with fresh and wet pine and mixed forests (Antenetea glutinosae vegetation class). The narrow ecological amplitudes and possible changes in habitat can lead to the extinction of this species in found localities. The most significant threats are long periods of drought in the summer season, increasing soil richness or soil acidity changes due to anthropic transformation and, as a consequence, the appearance of nitrophilic and eutrophic plants. The Middle-Dnieper forests have viable populations of sporophytes at the southern limit of their distribution, which makes it important to organize protection measures and ensure capabilities for its reproduction and distribution. To achieve this, surveys of the forests in the Middle Dnieper region designated for main-use fellings with types of forest vegetation conditions (according to the Pohrebniak scale) A2-3 will be relevant to be conducted, and areas with the growth of this species will be prohibited. Additionally, mechanical removal of shrubs and grasses of alien origin that are competitively dangerous for these and growing nearby habitats will be necessary.